Painting, Poetry and the Interference of the Genres in English Art: The Case of William Blake - Karaçoban, Atanas; Dita, Patricia Denisa (Border Crossing, 2020)
Throughout the history of Western culture and art, there are numerous examples of those who, in their creativity, went beyond the limits of a particular art, embarking instead on attempts to combine in one artistic discourse the practices of various arts, such as music and poetic text, drama and dance, literature and sculpture, literature and painting, and so on. One of these artists is William Blake, acclaimed as a major poet and painter of romanticism in English and world art. He is accredited as the founder of a whole new and original method of producing artistic works, called “illuminated printing”, which is a remarkable combination of poetic text, decoration, and picture. Apart from revealing Blake’s appurtenance to romantic tradition, the present study aims to present the specificity of his technique and, primary, to disclose the ways in which it combines the artistic practice of poetry with that of painting as to render and strengthen the meaning by mutually sustaining and illuminating each other.